2018
DOI: 10.1016/j.amepre.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Counseling in Clinical Settings: An Updated Systematic Review

Abstract: Context: The objective of this systematic review was to update a prior review and summarize the evidence (newly identified and cumulative) on the impact of contraceptive counseling provided in clinical settings. Evidence acquisition: Multiple databases, including PubMed, were searched during 2016–2017 for articles published from March 1, 2011, to November 30, 2016. Evidence synthesis: The search strategy identified 24,953 articles; ten studies met inclusion criteria. Two of three new studies that examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
4
16
0
3
Order By: Relevance
“…However, to assess the most effective approach, more detail is needed on how such education and counselling activities are conducted. This finding also supported the conclusions of other systematic reviews on the positive impact of this approach [51,52].…”
Section: Effectiveness Of Demand Generation Interventions With Regardsupporting
confidence: 90%
“…However, to assess the most effective approach, more detail is needed on how such education and counselling activities are conducted. This finding also supported the conclusions of other systematic reviews on the positive impact of this approach [51,52].…”
Section: Effectiveness Of Demand Generation Interventions With Regardsupporting
confidence: 90%
“…The current study conclusions are congruent to the conclusions of the study by Zapata, Tregear, Curtis, Tiller, Pazol, Mautone-Smith, and Gavin [9] on impact of Contraceptive Counselling in Clinical Settings. The study concluded that a robust positive association between counselling and uptake of contraceptives.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous researches have established the relationship between the two. In a study that analysed 23 studies by Zapata, Tregear, Curtis, Tiller, Pazol, Mautone-Smith, and Gavin [9] on impact of Contraceptive Counselling in Clinical Settings, the study established a robust positive association between counselling and uptake of contraceptives. The study explored the impact on studies carried out on different age groups to include adolescents, and adults and all indicated a positive impact on contraceptive performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La U.S. Preventive Services Task Force 84 propone el cribado por encima de 65 años (grado B de recomendación) y en mujeres más jóvenes que tengan un riesgo de fracturas similar (en torno al 10% en los próximos 10 años). En población española, el riesgo de fracturas en torno al 10% se alcanza en mujeres a los 72 años.…”
Section: Cribado De Osteoporosisunclassified